Regulations and Financial Services Advertising: Measuring the Financial Impact of Advertising Campaigns (Journal of Advances and Scholarly Researches in Allied Education, 2012)
It is critical to measure and record sales levels andother advertising responses following an ad campaign in order to determine thefinancial effects of the invested advertising dollars. Such measures may helpfine-tune the advertising strategy of the company and provide estimates foroptimizing future advertising campaigns.  For direct advertising campaigns, such measures  are  obtained through  the  tracking of  consumer  inquiries following the ad campaign and theuse of tracking numbers,  which canpinpoint the exact promotional material to which the consumers are reacting.